Perencanaan Strategi SI/TI Untuk SMP Menggunakan Enterprise Architecture Planning - Belsana ButarBUtar; Muhammad Haddiel Fuad; Alif Aflah Azzikri (Jurnal INSAN: Journal of Information System Management Innovation, 2022)
In the future development of data processing will be increased in line with the development of increasingly complex enterprise. Many Enterprise failure due to lack of careful planning that includes all elements of the organization. Enterprise will require data and information that accurate, timely and relevant for all parts that fit the needs of the business as well as the sharing of data between organizational units. To accommodate these needs can be done by increasing the utilization and strategy support SI/IT in the planning, implementation and control requires alignment with business strategy. Information system development aims to achieve the vision and mission of information system Junior high school in order to provide quality of data/information for the sake of business. The first step of achieving the vision and mission of this information system is to plan the information system to identify information needs and possible innovations in the use of technology to improve enterprise performance. Planning can use Enterprise Architecture Planning (EAP) methodology which result blueprint of the architecture data, application architecture, technology architecture and implementation plan for the enterprise In this research, a study case for planning of integrated information system development using EAP with applying value chain model and analisys approaches and tools is performed on Junior high school. The result in these cases study is the enterprise model, information resource catalog documentation, data architecture, application architecture, technology architecture and implementation plans